Granular computing : analysis and design of intelligent systems - Pedrycz, Witold, 1953- (Boca Raton : CRC Press, 2013)
"Given the nature of the technology, granular computing cuts across a broad range of engineering disciplines. This self-contained book builds upon introductory ideas and provides with illustrative examples that help facilitate a better grasp of more advanced material and enhance its overall presentation. It will be of a particular appeal to those engaged in research and practical developments in computer, electrical, industrial, manufacturing, and biomedical engineering. It will be equally well suited for those coming from non-technical disciplines where information granules assume a highly visible position"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Granular computing; Electronic books